Gene Polymorphism Associated With Acute Respiratory Distress Syndrome (Ards): A Literature Review - Ari Wahyuni; Zen Hafy; Debby Handayati Harahap; Syazili Mustofa (Universitas Pahlawan Tuanku Tambusai, 2026)
Gene polymorphisms can influence susceptibility, severity, and prognosis of ARDS. Genetic studies in ARDS have evolved from studies focused on candidate genes to studies that rely on a hypothesis-free approach to identify novel loci associated with ARDS risk or severity. In this review we outline the role of gene polymorphisms in ARDS susceptibility, severity, and prognosis. Several academic search engines were used in the literature search, including EMBASE/Elsevier. Science Direct, PubMed Central, Google Scholar, and Cochrane Review. Two subtopics were searched using Boolean Operators with keywords (ARDS OR acute respiratory distress syndrome) and (polymorphism) AND (ARDS) OR (genetic polymorphism) AND (ARDS) OR (polymorphism in ARDS). The studies retrieved discussed the impact of gene polymorphisms associated with ARDS including genes encoding interleukin 6 (IL-6), interleukin 10 (IL-10), vascular endothelial growth factor A (VEGF), angiotensin converting enzyme (ACE), interleukin 1 receptor antagonist (IL1RN), Fms Related Receptor Tyrosine Kinase 1 (FLT1) and Inducible Factor-1α (HIF-lα). These genes support significant associations and are involved in the regulation of gene expression associated with ARDS risk. Polymorphisms of IL-6, IL-10, VEGF, ACE, IL1RN, FLT1, HIF-lα play a role in susceptibility, severity, and prognosis of ARDS.